User Experience Analysis of TikTok’s Food Voucher Feature Using the System Usability Scale Method - Nur Fitriana Fajrin; Nurajijah Nurajijah (Komunitas Dosen Indonesia, 2026)
TikTok was initially introduced as a short-form video-sharing application, yet over time it has diversified its services by embedding various digital commerce features, including in-app food voucher promotions. Through this functionality, users can conveniently obtain and redeem discounted meal offers without leaving the platform, illustrating its strategic positioning within the social commerce ecosystem. Despite the feature’s frequent use among consumers, structured academic investigations examining its usability effectiveness are still relatively scarce. Accordingly, this research explores both usability performance and user experience of the food voucher feature by applying the System Usability Scale (SUS) as the primary evaluative instrument. The study adopted a descriptive quantitative methodology, collecting responses from 298 individuals who had prior experience using the feature. Before conducting the main statistical procedures, the questionnaire items were subjected to validity and reliability testing to ensure measurement accuracy and consistency. The analysis produced a SUS score of 72.15, suggesting that the feature achieves an acceptable and reasonably strong level of usability. In addition, Pearson correlation analysis identified a significant positive relationship between perceived usability and overall user experience (r = 0.579; p < 0.001). Although the findings indicate generally favorable performance, enhancements in navigational clarity, interface coherence, and user comfort are recommended to further elevate satisfaction levels.